2012
DOI: 10.1007/s10826-012-9668-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Behavioral Determinants of Mental Health Service Use by Urban, Under-Resourced Black Youth: Adolescent and Caregiver Perspectives

Abstract: Black adolescents with mental health problems are less likely than non-Black adolescents with mental health problems to receive treatment, primarily for non-financial reasons including negative perceptions of services and providers, and self-stigma associated with experiencing mental health problems. To better understand these obstacles, 16 adolescents and 11 caregivers, recruited from two K-8th grade elementary-middle schools, participated in four focus groups guided by the unified theory of behavior to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 64 publications
(85 reference statements)
5
90
0
Order By: Relevance
“…Previous research points to several barriers to engaging adolescents in MHS, including fear of stigma regarding mental health, as well as uncertainty around what to expect from MHS and if such services would be helpful (e.g., Lindsey et al, 2013; Thompson, 2013). Consistent with these findings, during the focus group, school nurses who participated in the current study reported these to be challenges that they faced when discussing mental health issues with youths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research points to several barriers to engaging adolescents in MHS, including fear of stigma regarding mental health, as well as uncertainty around what to expect from MHS and if such services would be helpful (e.g., Lindsey et al, 2013; Thompson, 2013). Consistent with these findings, during the focus group, school nurses who participated in the current study reported these to be challenges that they faced when discussing mental health issues with youths.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is comparable to adolescents’ service utilization in specialty mental health settings, where one would expect rates to be lower due to geographic, transportation, and scheduling barriers. In studies of adolescents’ help-seeking behaviors and attitudes toward MHS, adolescents identified stigma of mental health and privacy concerns (e.g., fear of being teased or gossiped about by peers) as major barriers to seeking MHS (Lindsey, Chambers, Pohle, Beall, & Lucksted, 2013; Thompson et al, 2013). Adolescents also expressed some hesitation about whether MHS would be useful and were generally uncertain of what to expect from services (Thompson et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests service users of Black ethnicities underuse mental health services (Doyle et al, 2012;Lindsey et al, 2013;Nadeem et al, 2007) and are more likely to experience adverse pathways to mental healthcare (Ayalon and Alvidrez, 2007;Commander et al, 1999;Morgan et al, 2005). Future research would benefit from focusing on mental healthcare perceptions within caregivers of Black ethnicities.…”
Section: Stigma-related Treatment Barriers: Caregiversmentioning
confidence: 99%
“…Fear of stigmatization regarding mental health, as well as uncertainty about what to expect from mental health services have also been identified as barriers to mental health treatment engagement (Lindsey, Chambers, Pohle, Beall, & Lucksted, 2013; Thompson et al 2013). How these factors specifically affect treatment engagement is not well understood.…”
Section: Introductionmentioning
confidence: 99%